Pengelolaan Kelas: Desain Lingkungan Positif Berdasarkan Interaksi Psikis dan Sosial Antara Siswa dan Guru di SMPN 2 Denpasar - Oka, Ni Putu Putri Ditha Sumaridewi; Karja, I Wayan; Trisnawati, Ida Ayu (Jurnal Penelitian Mahasiswa Indonesia, 2024)
Education is the main foundation for human growth in an ever-developing world. In this context, the learning environment in the classroom is a crucial factor that influences the effectiveness of the learning process. The researcher applied a qualitative phenomenological approach in completing this research to understand how the psychosocial and physical environment of the classroom at SMPN 2 Denpasar influences the learning process. A conducive class is the main focus, considering various aspects ranging from cleanliness, freedom to learn, to student-teacher social interaction. The role of a teacher who serves as a class manager who is responsible for creating a learning environment that motivates students as well as teachers. The research results highlight that a conducive classroom environment does not only involve physical aspects such as room layout, but also social and psychological aspects. Positive social interactions, students' freedom to learn, and camaraderie in the classroom influence their learning motivation. Organizing the classroom environment holistically is an important key in increasing the effectiveness of the learning process. Teachers need to understand their role in creating a learning atmosphere that stimulates student learning motivation. By paying attention to these aspects, the learning process becomes effective and is able to improve student learning outcomes.